Feasibility and acceptability of studying full-time nurse faculty salaries - Kathryn J. Malin; Jessica Zemlak; Jaqueline Christianson; Jessica Leiberg; Lisa Grabert (BMC, 2024)
Abstract Background The nursing shortage is driven, in part, by the critical shortage of nursing faculty. Consequently, qualified potential nursing students are being turned away from nursing schools each year. The preeminent issue influencing the United States nurse faculty workforce shortage is salary; financial compensation is higher in clinical and private-sector settings than educational settings. The purpose of this study is to describe current full-time nurse faculty salary, sources of income, and perceived need for more income, as well as the feasibility and acceptability of research focused on full-time nurse faculty salaries, so to guide future nursing faculty workforce research. Methods Using a cross-sectional study design, full-time nursing faculty working in a Midwestern state in the United States completed a survey inclusive of fixed choice and free text response options focused on income (individual gross, faculty, and secondary), demographics, and feasibility/acceptability of the survey instrument. Descriptive statistics were used to describe salary, sources of income, and perceived need for additional income. Feasibility and acceptability were evaluated by descriptive statistics examining three feasibility and acceptability questions, and by comparing demographic differences between participants who answered income questions compared to those who did not using t tests, x 2 tests, and Wilcoxon signed rank tests. Results One hundred and eighty-three full-time nurse faculty completed the survey in six weeks, representing 27% of the full-time nurse faculty workforce in the state. Over half of participants, 57%, reported having another job(s) in addition to their full-time faculty position to support basic living expenses. Most respondents reported willingness to share financial/salary data and viewed the survey to be acceptable. Conclusions Research focused on nursing faculty salaries was feasible and acceptable to those who chose to participate in the study. Perceived income needs may be an important factor driving career decisions for nursing faculty. Future research should focus on delineating how salary influences the decision to enter or stay in the nursing faculty workforce. Further, this study can inform policy recommendations on how to best measure and report nurse faculty salary and the gap between clinical salaries and faculty salaries.